Modulation of sperm function by estrogen and progesterone using in vitro experiments: A systematic review - Muloongo C. Sitali; Madalitso Chelenga (PLoS ONE, 2025)
Background The steroid hormones progesterone (P4) and Estrogen (E2) are essential for reproduction in both male and female mammals. Steroid hormones can alter sperm function in vitro via several mechanisms, thereby facilitating fertilization of female germ cells. The purpose of this systematic review is to investigate the in vitro experimental models that are used to understand the functionality of sperm after receiving supplementation with E2 and P4 in samples obtained from animal species using sperm oviductal epithelial cells (OECs) co-cultures and cultures of sperm in culture media only without OECs. Methodology A systematic literature search was conducted using Web of Science, Google Scholar, and PubMed to examine in vitro experimental models involving E2 and P4, aiming to understand sperm functionality in animals with or without OECs in culture media. A total of 32 out of 660 retrieved articles met the inclusion criteria, from which data were extracted, synthesized, and presented in a descriptive format. Results Sperm and oviducts from hamsters, mice, rats, monkeys, porcine, ovine, and bovine were used. Steroids E2 and P4 were administered at varying doses, either individually or in combination, with several studies observing dose-dependent effects on sperm function. In sperm-OECs co-cultures, P4 consistently promoted sperm hyperactivation, capacitation, and acrosome reaction (AR) via CatSper channel mechanisms, facilitating sperm release from OECs. Contrastingly, E2 delayed capacitation while enhancing sperm binding to the OECs. Similarly, supplementation of P4 in culture media alone without OECs induced sperm AR and capacitation, altered sperm motility, and improved in vitro fertilization (IVF) rates. Variations in motility and the binding ability of sperm to the isthmus and ampulla were reported in some studies. Conclusion The in vitro studies revealed that E2 and P4 alter sperm behavior dependent on dose, and improve sperm fertilizing ability in IVF programs across species. Future studies should focus on investigating and clarifying the species-specific sperm mechanisms following steroid hormone supplementation to enhance our understanding and improve the assisted reproductive technology outcomes.